Development of a training program to facilitate the implementation of the six ministerial priorities by professional nurses in Limpopo Province Health Care Facilities, South Africa - Legodi, Elizabeth Mmalehu (My University, 2022)
The purpose of this study was to develop a training programme to facilitate the implementation of the 6 Ministerial Priorities by Professional Nurses in the Health Care facilities in Limpopo Province. The purpose of the training programme was to capacitate the Professional Nurses to enable them to facilitate the implementation of the 6 Ministerial Priorities in the Health Care facilities of Limpopo to improve the provision of quality service. The study was conducted in three phases, namely, qualitative, quantitative and development of a training programme. Phenomenological semi structured one-to-one interviews were conducted to explore the perceptions of Professional Nurses on the implementation of the 6 Ministerial Priorities in the public hospitals in Limpopo Province. Interviews were conducted until saturation was reached. Themes and sub-themes were coded manually. The results of the qualitative phase were used to develop a questionnaire for the quantitative phase. Self-administered quantitative questionnaires were given to Professional Nurses to describe their experiences, knowledge and perceptions on the implementation of the 6 Ministerial Priorities in the Health Care facilities of Limpopo. The results that emerged from the integration of qualitative and quantitative results revealed that 6 Ministerial Priorities were not implemented effectively in the Health Care facilities due to challenges such as shortage of Professional Nurses and cleaners, shortage of cleaning material, linen and patients clothing. Shortage of medication, lack of in-service training on the 6 Ministerial Priorities and lack of orientation programme for the newly appointed Professional Nurses. These challenges affected the implementation of 6 Ministerial Priorities negatively thus compromising the provision of quality patient care. The training programme was developed for Professional Nurses to capacitate them on the facilitation of the implementation of the 6 Ministerial Priorities to improve quality care.
Thesis (Ph.D. (Nursing Science)) -- University of Limpopo, 2022
Keywords: Develop; Training Programme; Facilitate; Implementation; Professional Nurses; 6 Ministerial Priorities; Nurse practitioners; Nurses; Nurses -- In-service training; Health facilities